Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah (SAK EMKM) Pada Toko Tani dan Ternak Samarinda (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
The financial report is a tool for analyzing the financial performance of companies that can provide information about the financial position and performance, so it can serve as a basis for decision making by management. The objective of this research is to help business people in understanding the implementation of SAK EMKM as a new standard in financial reporting for MSMEs. Where UMKM can design a simple financial accounting system that can assist and simplify the making of financial statements based on SAK EMKM. This research uses descriptive method and data retrieval is done by interview and direct observation to Farm and Livestock Shop. This study was conducted to identify the constraints faced by MSMEs in the preparation of financial statements and preparing financial statements in accordance with SAK EMKM.The results of this study indicate that Farmers and Livestock Farmers have difficulties in preparing financial statements due to lack of human resources who have the ability in the field of accounting. The results of the preparation of financial statements based on SAK EMKM consist of statements of financial position, income statement, and notes to the financial statements.Keywords:Financial report, MSMEs, SAK EMKM